Pengembangan Media Mphyta Pembelajaran Materi Teorema Pythagoras untuk Kelas VIII SMP Negeri 5 Bojonegoro - Pujianto, Dian; Trineke Manoy, Janet (Universitas Negeri Surabaya, 2024)
Abstract: This research aims to describe the process and results of developing mpytha learning media assisted by construct 2 software. This research is development research using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used include media validation sheets for media experts, media validation sheets for material experts, student response questionnaire sheets and pretest-posttest sheets. Based on the results of research that has been carried out, the average validity value is 3.26 out of 4 with a percentage of 81.5% by media experts and 3.1 out of 4 with a percentage of 77.5% from material experts so it can be categorized as Mpytha learning media. valid. This learning media trial was carried out on a limited basis with 30 students in class VIII-J of SMP Negeri 5 Bojonegoro to obtain data on practicality (student response questionnaire) and media effectiveness (pretest-posttest sheet). The results of the research after the media were tested and evaluated, it was found that the learning media was declared practical in the medium category with a score of 2.91 or a percentage of 72.9%. The effective criteria obtained from the pretest-posttest results were declared effective in the medium category with an N-Gain value of 0.43.